2015
DOI: 10.1163/15685411-00002832
|View full text |Cite
|
Sign up to set email alerts
|

Plant-parasitic nematode feeding tubes and plugs: new perspectives on function

Abstract: Sum m ary -Several structures associated with feeding by plant-parasitic nematodes have been described using two terms, feeding tubes and feeding plugs. However, both of these terms encompass multiple structures of independent evolution, some of which are functionally distinct. We have reviewed the literature on both structures and provide a new perspective on the function of intracellular feeding tubes to maintain the integrity and efficacy of the feeding site. We propose that they provide sufficient hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Hereafter, Clade 3 genes are thus referred to as GS-like effector genes. While it is highly unusual for a 100 kilodalton pathogen effector to be translocated to the host cell cytoplasm (GS-like effectors are obligate homo-dimers of 50 kDa per subunit, S4 Fig ), plant parasitic nematodes clearly have the ability to construct organelle-sized structures inside the host cell at the plasma membrane where it meets the stylet orifice (reviewed in [ 32 ]). The demonstrations that a native GS-like effector protein is secreted from the nematode, delivered into the host, translocated across the host plasma membrane, and localised within the host cell during parasitism are strong evidence of involvement in parasitism.…”
Section: Resultsmentioning
confidence: 99%
“…Hereafter, Clade 3 genes are thus referred to as GS-like effector genes. While it is highly unusual for a 100 kilodalton pathogen effector to be translocated to the host cell cytoplasm (GS-like effectors are obligate homo-dimers of 50 kDa per subunit, S4 Fig ), plant parasitic nematodes clearly have the ability to construct organelle-sized structures inside the host cell at the plasma membrane where it meets the stylet orifice (reviewed in [ 32 ]). The demonstrations that a native GS-like effector protein is secreted from the nematode, delivered into the host, translocated across the host plasma membrane, and localised within the host cell during parasitism are strong evidence of involvement in parasitism.…”
Section: Resultsmentioning
confidence: 99%
“…The J2 feeds on the syncytium contents using a feeding tube that is produced during each feeding cycle. It has been suggested that this acts as a filter to prevent destruction of the feeding site, which the nematode must keep alive for the duration of the life cycle (Eves‐van den Akker, Lilley, Jones, et al., 2015). Once the feeding site is established and feeding has commenced, the nematode develops through a further three moults to the adult stage.…”
Section: Life Cyclementioning
confidence: 99%
“…The delivery of pharyngeal gland secretions and extraction of assimilates by feeding nematodes occurs in repetitive cycles in which salivation and feeding phases are intermitted by a preparation phase marked by stylet retraction and reinsertion. For many lineages of plant parasitic nematodes, the salivation phase is associated with the formation of an intracellular feeding tube, the nature of which is not fully understood (Eves-van den Akker et al, 2015). However, it is thought that these feeding tubes function as molecular sieves enabling the selective uptake of small molecules from the host cell cytoplasm.…”
Section: Parallel Adaptations In Nematodes and Associated In Host Celmentioning
confidence: 99%